FAKTOR-FAKTOR YANG MEMPENGARUHI ONLINE REPURCHASE INTENTION SHOPEE DI JAKARTA TIMUR - UTAMI, SISKA PUTRI; HIDAYAT, MUWAFICK (E-Jurnal Manajemen Trisakti School of Management (TSM), 2024)
This study aims to examine and analyze how Customer Satisfaction, Adjusted Expectation, Perceived Value and Perceived Usefulness To Online Repurchase Intention affect Shopee customers in East Jakarta. The research design uses descriptive and causal research by measuring all variables using a Likert scale consisting of 5 points. This study uses primary data by collecting data through questionnaires. The sampling technique used was a purposive sampling method which was done by distributing questionnaires to 262 respondents. In this study using statistical methods with SMART PLS 3.2.9 as a test tool. The results of this study indicate that Customer Satisfaction has no effect on Online Repurchase Intention, whereas Adjusted Expectation, Perceived Value and Perceived Usefulness effect on Online Repurchase Intention.